Dinamika Konsumsi Rumah Tangga Sektor Restoran dan Hotel sebagai Dalam Meningkatkan Investasi Nonbangunan di Pulau Kalimantan - Prasetyo Yuli Usaid (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Gross Fixed Capital Formation (GFCF) in non-construction assets is an important indicator for describing productive investment activities in a region, particularly investments that are flexible and responsive to economic dynamics. Within the regional economic structure, service sectors such as restaurants and hotels play a strategic role as drivers of domestic consumption–based economic activity. This study aims to analyze the effect of household consumption in the restaurant and hotel sector on non-construction GFCF in Kalimantan Island. The study employs a quantitative approach using a simple linear regression method. The data used are secondary data on Gross Regional Domestic Product (GRDP) by expenditure at constant prices, obtained from Statistics Indonesia (BPS), covering five provinces in Kalimantan Island over the period 2020–2024. The results indicate that household consumption in the restaurant and hotel sector has a positive and significant effect on non-construction GFCF. These findings suggest that increasing demand for restaurant and hotel services encourages business actors to adjust and expand their operational capacity through non-construction investments, such as the acquisition of equipment, machinery, service technologies, and supporting operational facilities. However, the magnitude of the effect of consumption on non-construction investment varies across provinces, reflecting differences in regional economic structures. Overall, the study confirms that household consumption in the restaurant and hotel sector serves as an important basis for promoting non-construction investment formation and supporting regional economic development in Kalimantan Island.